Seroepidemiologic Survey of Canine Visceral Leishmaniasis in Tehran and Alborz Provinces of Iran. - Abdolali Malmasi; Saeedeh Janitabar; Mehdi Mohebali; Behnaz Akhoundi; Nadi Maazi; Mehdi Aramoon; Narges Khorrami; Hesam A Seifi (Tehran University of Medical Sciences, 2014)
Background: A two year seroepidemiological study was designed to find out the seroprevalence and risk factors ofcanine visceral leishmaniasis (CVL) among stray and owned dogs in Tehran and Alborz Provinces of Iran. Methods: Blood samples of  602 dogs living in  11  counties of  Tehran and  Alborz  Provinces were  taken by venipuncture in 2008-2010. After separation of blood sera, anti-leishmanial antibodies were detected by direct agglutination test (DAT). Results: Overall, of the 408 and 194 serum samples collected randomly from dogs in 11 localities in Tehran and Alborz Provinces, 18/408 (4.41%) and 12/194 (6.18%) respectively were found positive. Among the localities, Shemiran in Tehran Province and Karaj In Alborz Province had the highest prevalence rates. No statistically significant differences were found between sex and living place but there was significant difference between living status (owned or stray) and CVL infection of dogs in Alborz Province (P= 0.018). The highest seroprevalence (7.5%) was found in dogs aged 3 to 5 years old. Only 20% of the seropositive dogs were symptomatic. Conclusion: Concerning possible human infections in Tehran and Alborz Provinces, both symptomatic and asymptomatic seropositive dogs should be considered as a risk.